Penerapan E-Commerce Content Management System Menggunakan Metode Business Model Canvas Studi Kasus Qorina Garden - Abi Nala Wiatma; Grace Gata; Anita Ratnasari (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2021)
Qorina Garden is a line of business that is engaged in the sale of ornamental plants that was established in September 2020. Currently all transactions at Qorina Garden are carried out in the conventional way, namely by meeting face to face or via whatsapp chat. This is a problem for Qorina Garden because conventional sales will be limited by the scope of time and distance between the seller and the buyer. For this reason, after conducting interviews and observations, astore is needed online -based website e-commerce that is able to provide detailed information to customers. website Thiswas created using the Content Management System WordPress and plugins supporting. This website was developed using the methods Business Model Canvas and Unified Modeling Language. In this website there are features to input product data, create product categories, process orders, verify payments, and print reports every month to find out the profit of sales. So it is hoped that with this website, Qorina Garden will have a positive impact in the form of a wider marketing coverage so that it is able to answer sales problems and can increase sales and income at Qorina Garden